2012
DOI: 10.1134/s1063784212050234
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the poiseuille flow in a longitudinal magnetic field

Abstract: The stability to small perturbations of a 2D flow of a conducting viscous fluid with large Reynolds numbers in a longitudinal magnetic field is investigated. A complete linearized system of magnetohydrody namics equations is considered using the method of collocations and the differential sweep method. The dependences of the critical Reynolds numbers on the electrical conductivity are analyzed in detail. A new instability branch for large Reynolds numbers and a jumpwise variation of the critical Reynolds numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The magnetic Prandtl number P m = R m /R e ∝ ν/η and measures the ratio of the dissipative effect of flow (viscosity) and the magnetic field (resistivity). Previous studies indicate that P m plays an important role in both the instabilities of shear flow and a shear magnetic field [24]. Thus, the roles of P m in the unstable spectra of PF are numerically calculated in this subsection.…”
Section: Roles Of the Magnetic Prandtl Numbermentioning
confidence: 97%
See 1 more Smart Citation
“…The magnetic Prandtl number P m = R m /R e ∝ ν/η and measures the ratio of the dissipative effect of flow (viscosity) and the magnetic field (resistivity). Previous studies indicate that P m plays an important role in both the instabilities of shear flow and a shear magnetic field [24]. Thus, the roles of P m in the unstable spectra of PF are numerically calculated in this subsection.…”
Section: Roles Of the Magnetic Prandtl Numbermentioning
confidence: 97%
“…In the threedimensional calculation, it is found that the assumption used to obtain the modified Orr-Sommerfeld equation [20] is not suitable [22]. Even in the two-dimensional (2D) calculation, if the assumption of a small Reynolds number is abandoned, the calculation of the stability equation of the sixth-order ODE for the incompressible MHD flow indicates a new instability branch for a large Reynolds number [23,24]. However, in [23,24], the stability curves are obtained by fixing the magnetic Prandtl number P m = R m /R e ∝ ν/η, where ν and η are the viscosity and the resistivity of the fluid medium, respectively, which only infers that the new instability branch is excited in the region when the Reynolds number and magnetic Reynolds number R m = P m R e are both large.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that, in solving problems of magnetohydrodynamics, the analog of the Poiseuille solution is the Hartmann flow [20,23]. The superposition of the Poiseuille and Hartmann flows was studied in [14,32,37,38]. In addition, the exact Poiseuille solution was used in the hydrodynamics of non-Newtonian fluids in [1,10,12,13,15,24,25,30,46].…”
Section: Introductionmentioning
confidence: 99%